2002
DOI: 10.1590/s0102-05362002000400002
|View full text |Cite
|
Sign up to set email alerts
|

Uso de nomes populares para as espécies de Araceae e Dioscoreaceae no Brasil

Abstract: A origem dos nomes vulgares das espécies muitas vezes é obscura ou mesmo impossível de ser identificada. Face à semelhança que apresentam alguns tipos de sistema subterrâneo de Dioscorea com aqueles das espécies de Colocasia, observa-se em muitos trabalhos publicados na literatura brasileira uma certa confusão na terminologia usada para definir estruturas principalmente em algumas espécies de "inhame" e "cará". A padronização no Brasil da nomenclatura das estruturas subterrâneas destas hortaliças, à luz dos "C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
23

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 7 publications
0
10
0
23
Order By: Relevance
“…Like other vegetative propagated crops, yams are cultivated and maintained by farmers for their agrobotanical, taxonomic or gastronomical characteristics, and because of that, several names are assigned to new local varieties when they are introduced in the homegardens (Chair et al, 2010). Some authors (Asemota et al, 1996;Dansi et al, 1999;Pedralli et al, 2002) observed a considerable variation in linguistic terms in the nomenclature of the local yam varieties, where each location has its own variable names for different cultivars.…”
Section: Characterization Of the Folk Nomenclature For Dioscorea Alatamentioning
confidence: 99%
“…Like other vegetative propagated crops, yams are cultivated and maintained by farmers for their agrobotanical, taxonomic or gastronomical characteristics, and because of that, several names are assigned to new local varieties when they are introduced in the homegardens (Chair et al, 2010). Some authors (Asemota et al, 1996;Dansi et al, 1999;Pedralli et al, 2002) observed a considerable variation in linguistic terms in the nomenclature of the local yam varieties, where each location has its own variable names for different cultivars.…”
Section: Characterization Of the Folk Nomenclature For Dioscorea Alatamentioning
confidence: 99%
“…They are angiosperms and a member of the monocotyledonous family, Dioscoreaceae. The genus Dioscorea comprising over 650 species distributed throughout the World's tropical, subtropical and temperate regions [2][3]. The Dioscorea genus includes an important group of tropical food yams, the edible portion of which is the tuber, and occasionally the bulbil.…”
Section: Introductionmentioning
confidence: 99%
“…More than 800 species of Araceae have economic (ornamental, edible or medicinal) or ethnobotanic importance, and about 10% of the world population use as food ingredient the taro rhizome Colocasia esculenta (L.) Schott, popularly known in most countries like "taro" (Pedralli et al 2002). Due to peculiar characteristics such as rusticity and nutritional values, taro is a tuberous species suggested by FAO (Food and Agriculture Organization) as an alternative crop to increase the food base in developing countries .…”
Section: Introductionmentioning
confidence: 99%